Bridging the Digital Divide: The Role of Female Principals in Advancing 4IR in Rural South African Education - Thembi Busisiwe Nkosi; Zvisinei Moyo (STAI Miftahul Ula Nganjuk, 2025)
Women principals in rural public primary schools have proven themselves to be the change agents despite the numerous constraints in leading the Fourth Industrial Revolution (4IR) in their schools. The purpose of this study was to describe the efforts of women principals leading the 4IR in public rural elementary schools in South Africa. The findings showed that all the respondents had started to integrate 4IR in both administrative and curriculum-related activities although their schools were in the early phases of the 4IR. They indicated that there had been continuous progress in 4IR as teachers and learners are using more e-learning materials, online sites, tablets, smart boards and Wi-Fi to support teaching and learning and in managing the school. In administration, the principals have introduced digital solutions to support school operations such as the South African Schools Administration and Management System (SA-SAMS) and Data Driven District (DDD) systems for administrative purposes, emails and social media for communications, and data analysis to keep track of learners’ performance. The women principals are also teaming up with various stakeholders who can assist in this direction such as their SGBs, technologically knowledgeable young teachers, parents, business and community partners. The principals have also shown themselves to be creative and resilient in the face of limited infrastructure and skills development for teachers and themselves. They are committed to continuous learning and professional development and demonstrate this through their development of a culture of innovation and questioning, as well as actively encouraging and facilitating their staff to be upskilled in ways which connect with 4IR skills. The women principals clearly demonstrated their influential roles by inspiring stakeholders to actively participate in the 4IR.